Developing an activity and absorption-based quality control platform for Chinese traditional medicine: Application to Zeng-Sheng-Ping(Antitumor B). (22nd August 2015) - Yin, Taijun; Yang, Guanyi; Ma, Yong; Xu, Beibei; Hu, Ming; You, Ming; Gao, Song
Abstract: Ethnopharmacological relevance: Zeng-Sheng-Ping (ZSP), also called antitumor B, is a marketed Chinese traditional medicine used for cancer prevention. Aim of the study: Currently, for the quality control of Chinese traditional medicines, marker compounds are not selected based on bioactivities and pharmaceutical behaviors in most of the cases. Therefore, even if the "quality" of the medicine is controlled, the pharmacological effect could still be inconsistent. The aim of this study is to establish an activity and absorption-based platform to select marker compound(s) for the quality control of Chinese traditional medicines. Materials and methods: We used ZSP as a reference Chinese traditional medicine to establish the platform. Activity guided fractionation approach was used to purify the major components from ZSP. NMR and MS spectra were used to elucidate the structure of the isolated compounds. MTT assay against oral carcinoma cell line (SCC2095) was performed to evaluate the activities. UPLC–MS/MS was used to quantify the pure compounds in ZSP and the active fraction. The permeabilities of the identified compounds were evaluated in the Caco-2 cell culture model. The intracellular accumulation of the isolated compounds was evaluated in the SCC2095 cells. Results: The major compounds were identified from ZSP. The contents, anti-proliferation activities, permeabilities, and intracellular accumulations of these compounds were also evaluated. The structure of these purified compounds were identified by comparing the NMR and MS data with those of references as rutaevine (1 ), limonin (2 ), evodol (3 ), obacunone (4 ), fraxinellone (5 ), dictamnine (6 ), maackiain (7 ), trifolirhizin (8 ), and matrine (9 ). The IC50 of compounds5, 6, and7 against SCC2095 cells were significantly lower than that of ZSP. The uptake permeability of compounds5, 6, and7 were 2.58±0.3×10 −5, 4.33±0.5×10 −5, and 4.27±0.8×10 −5 respectively in the Caco-2 cell culture model. The intracellular concentrations of these compounds showed that compounds5, 6, and7 were significantly accumulated inside the cells. Conclusion: Based on the activity against oral carcinoma cell line as well as the absorption permeability, compound5, 6, and7 are selected as quality control markers for ZSP. An activity and absorption-based platform was established and successfully used for the quality control of ZSP. Graphical abstract: